A vaccination campaign against rabies in Kenya - International Livestock Research Institute (International Livestock Research Institute, 2021)
The ILRI-led One Health Centre in Africa (OHRECA) in partnership with the Machakos County government, the Zoonotic Disease Unit (ZDU) and Vétérinaires Sans Frontières-Germany (VSF-G) have launched a rabies vaccination campaign in Machakos County as part of an effort to eliminate rabies in Kenya by 2030. World Rabies Day that takes place each year on September 28, the anniversary of the death of Louis Pasteur who, with his colleagues, developed the first efficacious rabies vaccine.